From Dialectics to Theo-Logic: The Ethics of War from Paul Ramsey to Oliver O’Donovan - Feiler, Therese (Studies in Christian ethics, 2015)
This article studies the fundamental shift between Paul Ramsey’s and Oliver O’Donovan’s ethics of war and so reintroduces Hegel into the debate on political ethics. The topic is approached through the notion of divine-human and political mediation, whereby Hegel’s early movement from Christology to dialectics provides the analytical framework. The article first studies the theo-logic of Paul Ramsey’s early agapist notions of war up to his transformist period. It then traces how O’Donovan fundamentally transforms Ramsey’s dialectical framework within that of narrated Christology. O’Donovan’s focus culminates in the unified reign of Christ and the overcoming of Hegel’s dialectics. But it is argued that the transition to Hegel’s and Ramsey’s perspectives is constantly required in order to prevent Christian ethics from becoming ossified. The article thus hopes to initiate a comprehensive, because logical-systematic discussion of contemporary wars and war machines, especially in critical conversation with philosophers and military practitioners.